Continuity and Change in Public Service News Online: A longitudinal analysis of the Norwegian Broadcasting Corporation. (16th November 2016) - Sjøvaag, Helle; Stavelin, Eirik; Moe, Hallvard
Abstract : This article presents a longitudinal big data analysis of the online news provision of the Norwegian Broadcasting Corporation (NRK). Comparing data from 2009 with data from 2013 (approximately 150, 000 news items), the analysis assumes a hybrid methodological approach combining human and computer coding to enquire about longitudinal trends in online journalism as produced by a public service institution in a competitive market. The analysis finds NRK's online news profile to be rather stable across the period, with increases in the areas of audiovisual streaming, linking practices, multimedia features and social media sharing as a result of technological developments. While a more dynamic front-page environment puts the broadcaster as a competitor in the overall online news market, an increase in self-promotional content also suggests NRK is moving towards a more pronounced broadcasting identity. As public service broadcasters are being increasingly challenged across Europe by claims of unfair competitive advantage, this analysis offers a much-needed empirical basis for discussing the role and function of public service broadcasting online.